A task‐ and role‐based perspective on super‐recognizers: Commentary on 'Super‐recognizers: From the lab to the world and back again'. (25th March 2019) - Moreton, Reuben; Pike, Graham; Havard, Catriona
Abstract : This article provides a commentary on recent work by Ramon et al . (2019, British Journal of Psychology ) on super‐recognizers. The commentary advocates a task‐ and role‐based approach to SR research and greater collaboration between researchers and the applied community.